2011
DOI: 10.1056/nejmoa1100102
|View full text |Cite
|
Sign up to set email alerts
|

STAT1Mutations in Autosomal Dominant Chronic Mucocutaneous Candidiasis

Abstract: Mutations in the CC domain of STAT1 underlie autosomal dominant CMC and lead to defective Th1 and Th17 responses, which may explain the increased susceptibility to fungal infection. (Funded by the Netherlands Organization for Scientific Research and others.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
461
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 618 publications
(483 citation statements)
references
References 29 publications
18
461
2
2
Order By: Relevance
“…Mutated STAT1 sequences were created from a modified STAT1-pRc/CMV vector (kind gift from Geeta Devgan) using site-directed mutagenesis (QuikChange Lightning Site-Directed Mutagenesis Kit; Stratagene) and primers (Supporting Information Table 2) previously described to create constructs carrying A267V and R274W mutant as well as WT STAT1 [5,6].…”
Section: Generation Of Gof-stat1 Vectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutated STAT1 sequences were created from a modified STAT1-pRc/CMV vector (kind gift from Geeta Devgan) using site-directed mutagenesis (QuikChange Lightning Site-Directed Mutagenesis Kit; Stratagene) and primers (Supporting Information Table 2) previously described to create constructs carrying A267V and R274W mutant as well as WT STAT1 [5,6].…”
Section: Generation Of Gof-stat1 Vectorsmentioning
confidence: 99%
“…As proof of principle, it was found that the candidiasis in patients with autoimmune polyendocrinopathy candidiasis ectodermal dystrophy who suffer with autoimmunity as a result of AIRE gene mutations was linked to autoantibodies against Th-17 cytokines (IL-17A, IL-17F, and IL-22), elegantly explaining the CMC in the context of autoimmunity [4]. However, about half of patients with isolated CMC (Online Mendelian Inheritance in Man #614162) were found to have an underlying gainof-function (GOF) STAT1 mutation [5,6], affecting the STAT1 signaling pathway not previously known to be directly involved in IL-17 production. Nevertheless, these patients have impaired in vitro Th-17 cell proliferation and IL-17 production in response to Candida stimulation [7] explaining their CMC, but the mechanisms through which the GOF-STAT1 mutation decreases STAT3-dependent production of Th-17 cytokines remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, its gain-of-function (GOF) mutations exhibit different immunological defects. The patients suffer from persistent or recurrent infection of the skin, nails, and mucous membranes with Candida albicans, referred to as chronic mucocutaneous candidiasis (CMC) (7)(8)(9). Assigning structural changes caused by these pathogenic amino acid substitutions has shed light on the molecular mechanisms of STAT1-mediated immunodeficiencies as well as the fundamental roles of the original residue in normal STAT1 functions.…”
mentioning
confidence: 99%
“…1B), it was initially postulated that the CCD acts as a docking platform for transcription factors to cooperatively support STAT1-mediated transcription and that GOF mutations in the CCD increased their interactions (12). Recently, another mechanism of STAT1 GOF was proposed (7,9). Dephosphorylation of Tyr-701 proceeds via anti-parallel conformation of the STAT1 dimer through phospho-Tyr-701-independent interaction between the CCD and DBD (13).…”
mentioning
confidence: 99%
See 1 more Smart Citation